Liver function is a predictor of survival in patients with hepatocellular carcinoma in best supportive care. (March 2023) - Campani, C.; Bucci, L.; Adotti, V.; Rosi, M.; Arena, U.; Trevisani, F.; Marra, F.; ,
Abstract : Background and Aims: The prognosis of patients with hepatocellular carcinoma (HCC) is very variable, and the relative contribution of tumor burden and liver dysfunction to survival is uncertain. Median overall survival (OS) of patients managed with best supportive care is around 3-6 months, although longer values may be observed in clinical practice. Aim of this study was to identify the factors linked to tumor or liver dysfunction associated with survival in patients with HCC treated with BSC. Methods: We retrospectively evaluated the clinical characteristics of 1414 patients who had an indication for BSC recorded in the Ita.Li.Ca. database between 2000 and 2020. We analyzed both patient and tumor characteristics to identify predictors of OS. Results: Median age was 69y and 76% of patients were male. Etiology included chronic viral infection (68.3%), alcohol use disorder (30.9%) and non-alcoholic steatohepatitis (8.3%). 67.4% of patients had a performance status 0-1 and 41.4% were in Child-Pugh B class. Median MELD was 13. 60% of patients had a multifocal HCC with a median number of 3 lesions and a median size of 33mm. 533 patients had vascular invasion. Median alpha-fetoprotein was 49.25 ng/ml. 111 patients were classified as BCLC-A, 148 as BCLC-B, 791 as BCLC-C and 325 as BCLC-D (12 unknown). No differences in terms of OS were observed considering the etiology of liver disease or the presence of cirrhosis. Obesity (p<0.001), hypercholesterolemia (p=0.036) and hypertriglyceridemia (p=0.034) were associated with lower OS. Absence of symptoms (6 vs 10 months, p<0.001), lack of vascular invasion (9.1 vs 5.03, p<0.001), and absence of metastasis (8.167 vs 4.733 p<0.001) were associated with a better OS. Survival in BCLC-A patients was longer than in stages B or C. Survival progressively declined according to severity of liver function using three different scores (CPS, ALBI, pALBI, p<001). Women tended to survive longer 23 vs. 19 months, p=0.053). Comparing patients surviving more or less than 12 months (398 vs. 1016), age, size of lesions, albumin, bilirubin, alpha-fetoprotein, and MELD were significantly different. At Cox univariate analysis presence of cirrhosis, number and size of lesions, vascular invasion, metastasis, ALBI and pALBI grades, MELD, and CPS were significantly associated with OS. Using different models to avoid colinearity ALBI, pALBI, and CPS maintained an independent prognostic role on OS. Conclusion: In a large series of patients with HCC in BSC, parameters of liver function are strongly associated with survival.